Reliance on Acute Care Settings for Health Care Utilization: A Comparison of Adolescents With Younger Children. Issue 12 (December 2021) - Goyal, Monika K.; Richardson, Troy; Masonbrink, Abbey; Reed, Jennifer L.; Alpern, Elizabeth R.; Hall, Matt; Neuman, Mark I.
Abstract : Objective: Because a goal of the Affordable Care Act was to increase preventive care and reduce high-cost care, the objective of this study was to evaluate current health care use and reliance on acute care settings among Medicaid-enrolled children. Methods: This was a retrospective cohort study of the 2015 Truven Marketscan Medicaid claims database among children 0 to 21 years old with at least 11 months of continuous enrollment. We calculated adjusted probabilities of health care use (any health care use and ≥1 health maintenance visit) and high acute care reliance (ratio of emergency department or urgent care visits to all health care visits >0.33) by age and compared use between adolescents and younger children using multivariable logistic regression. Results: Of the 5, 182, 540 Medicaid-enrolled children, 18.9% had no health care visits and 47.3% had 1 or more health maintenance visit in 2015. Both health care use and health maintenance visits decreased with increasing age ( P < 0.001). Compared with younger children (0–10 years old), adolescents were more likely to have no interaction with the health care system [adjusted odds ratio (aOR), 2.20; 95% confidence interval (CI), 2.19–2.21] and less likely to have health maintenance visits (aOR, 0.40; 0.39–0.40). High acute care reliance was associated with increasing age, with adolescents having greater odds of high acute care reliance (aOR, 1.08; 1.08–1.09). Conclusions: Medicaid-enrolled adolescents have low rates of health care use and have high reliance on acute care settings. Further investigation into adolescent-specific barriers to health maintenance care and drivers for acute care is warranted.